EFEK PERSUASI SOSIAL TERHADAP PERILAKU SISWA DALAM PROBLEM SOLVING KOPERATIF - Permatasari, Dewi (JSTT, 2015)
Qualitative analysis has been done on the effect of social persuasion toward students’ behavior in pair problem solving. The research subjects were two male students of Class XI from a senior high school in district of Parigi-Moutong. Each student in the group had different role. Both students also exchang role in the problem solving. One student was as a model to solve problems and another student was as an observer. The instrument of the study was a test that consisted of 3 items. The test was used to explore students’ behaviour during the pair problem solving. Semi-structured interviews were conducted in two phases. The first phase was after the problem solving and the second was after video analysis. The activities were recorded using video cameras: three cameras were in the problem solving and one in the interview. Based on data analysis, it can be stated that social persuasion is dominant aspect affecting self-efficacy beliefs of students in pair problem solving.